(untitled) (INNOVATIVE ECONOMY, 2026)
Chereshnyuk O.M. THE CONCEPT OF ACCOUNTING FOR SOLAR PANELS AND THEIR INTERNAL CONTROL AT ENTERPRISES Purpose. The aim of the study is to investigate approaches to accounting and internal control of solar panels as a specific object of fixed asset of enterprises. Methodology of research. The study uses the methods of analysis and synthesis (to examine scientific approaches to accounting for solar panels); generalization (to formulate conclusions regarding the economic essence of solar panels as an object of accounting); classification (to group the components of a solar power plant according to the relevant accounting sub-accounts); and a systematic approach (to consider solar panels as a complex object that combines investment, production, energy-saving, environmental and control functions). Findings. It has been established that a component-based approach is appropriate for the reliable accounting of a solar power plant, as its individual components differ in function, cost, useful life and wear intensity. It has been proved that accounting for solar panels should be organized taking into account the stages of their use: investment, operational and final. The main areas of internal control over solar panels have been proposed, including control over their availability, valuation, documentation, depreciation, maintenance and modernization costs, generated electricity, income or cost savings, technical efficiency, environmental results and write-off. Originality. The approach to accounting for solar panels as a specific object of fixed assets and to their internal control has been further developed, taking into account investment, production, energy-saving and environmental aspects. The accounting representation of a solar power plant has been improved through the use of component-based accounting of its elements, considering their different useful lives and functional purposes. Provisions for the organization of internal control over solar panels have been developed based on a combination of accounting information, technical indicators and digital monitoring systems. Practical value. The proposed provisions can be used in the activities of alternative energy enterprises and other business entities that install and use solar panels to generate electricity, reduce energy costs, and increase energy autonomy. Key words: accounting for solar panels, control over the use of solar panels, internal control, solar panels, fixed assets, alternative energy, renewable energy.